“94° à l'ombre” (Rennes - années 1990-2000). Le lien sonore par-delà la peine - Gaïd Andro; Fanny Le Bonhomme (Criminocorpus)
In 1995, the Rennes section of the GENEPI association launched the programme "94° à l'ombre" on the local radio station Canal B. Hosted by students, the programme aimed to establish a radio link between prisoners and their families. By analysing the radio archives (1996-1998) and the archives of the association, this article aims to contribute to the social history of the prison and the history of the radio medium at local level. By defining the media space as a shared social space, the analysis of these sources makes it possible to approach the experience of detention as a transversal social fact. What do these radio programmes give voice to? What do families and relatives have to say, and to whom? What can we understand about justice and detention as listeners and as historians?